Understanding digital literacy through the lens of young people’s everyday practices: insights from Singapore university students - Liang, Wei Jhen (2025)
Young people's digital practices have gained increasing attention in educational, social, and media research due to digital technologies' increasingly important role in shaping learning, identity, and social interactions. In our digitally mediated era, educators, policymakers, and researchers are focused on how best to integrate digital media into curricula and equip students with the competencies needed to navigate an increasingly digitalized society. This endeavor poses several challenges, including fostering digital skills to enhance online opportunities (Livingstone, Mascheroni, & Stoilova, 2023), adopting critical perspectives on digital capitalism (Buckingham, 2020), and nurturing digital citizenship to encourage ethical and socially responsible behavior (Buchholz, DeHart, & Moorman, 2020). At the heart of these efforts lies the concept of digital literacy, which has emerged as a crucial framework for preparing youths for life in a digital society. Scholars and educators advocate for digital literacy as a multifaceted competence encompassing technical skills, critical thinking, ethical participation, and creative content production (Pangrazio, Godhe, & Ledesma, 2020; Reddy, Sharma, & Chaudhary, 2020; Wuyckens, Landry, & Fastrez, 2022). Yet, as a broad and evolving concept, there remains a lack of consensus regarding its definition and scope. This lack of clarity is compounded by limited understanding of how young people’s everyday digital practices intersect with their development of digital literacy. Generation Z, often identified as “digital natives,” represents the first cohort to grow up immersed in digital technologies. Their familiarity with digital media has led to the assumption that digital literacy is an inherent skill. For instance, List (2019) observed that one-fifth of undergraduate students in the United States perceived digital literacy as an intrinsic competence acquired through exposure to digital technologies. However, such assumptions may obscure the complexities of digital literacy as both a skill set and a social practice. In higher education, where digital literacy is increasingly recognized as a critical 21st-century competency (Miranda, Isaias, & Pifano, 2018; Santos & Serpa, 2017), a deeper understanding of students’ perspectives and practices is essential. This paper seeks to bridge these gaps by investigating how university students in Singapore understand digital literacy and how these understandings shape and are shaped by their everyday digital practices. The study forms part of a larger research project examining the interrelationships between youths’ digital literacy experiences and their identities. Adopting a mixed-methods convergent parallel design, this research integrates quantitative and qualitative approaches to provide a comprehensive understanding of the topic. This methodological approach facilitated an exploration of both the “what” and “how” of digital literacy among Singapore university students. The quantitative phase of the study utilized a survey instrument developed from an extensive literature review consolidating three primary perspectives on digital literacy. After data cleaning, 918 valid responses were analyzed using SPSS. The sample was balanced in terms of gender and academic year distribution, with participants representing diverse academic disciplines. Statistical analyses, including one-way ANOVA with Scheffé's post-hoc tests, were conducted to explore relationships between students’ demographic profiles and their digital literacy perspectives. The qualitative phase involved semi-structured interviews with a subset of 25 survey respondents. These interviews delved into participants’ everyday digital practices, including their consumption and production activities, as well as their conceptualizations of digital literacy. Interview transcripts were systematically coded and analyzed to uncover nuanced insights into how students navigate digital spaces and how their understanding of digital literacy informs their practices. Preliminary results from the quantitative analysis reveal that digital literacy as individual cognitive competencies is the most prevalent perspective among undergraduate students in Singapore. This perspective, which emphasizes technical skills and cognitive abilities, showed the highest mean and lowest standard deviation, indicating strong and consistent agreement among students. Significant differences were observed in relation to gender and academic discipline. Results revealed that females scored significantly higher on this perspective than males and non-binary/third-gender individuals. Additionally, Communication Studies students scored statistically significantly lower on this perspective of digital literacy compared to their peers in Science and Social Sciences. These results illuminate how socio-demographic and disciplinary contexts shape students’ perspectives on digital literacy and highlight the diverse ways in which young people engage with digital technologies. By foregrounding students' voices, this study provides valuable insights into the nuanced relationships between digital literacy and everyday practices. In conclusion, understanding digital literacy through the lens of young people’s experiences offers a richer foundation for developing educational strategies that align with their needs and aspirations. As digital technologies continue to evolve, educators and policymakers must adopt flexible and inclusive approaches to equip students with the competencies necessary for navigating the complexities of the digital age.